Hubungan Dimensi Mutu Pelayanan Farmasi Rawat Jalan dengan Kepuasan Pasien di RS Baptis Batu: Peran Kepesertaan Asuransi - Megawati, Megawati; Hariyanto, Tatong; Rachmi, Asih Tri (Universitas Brawijaya, Indonesia, 2016)
This study aims to determine whether the level of user satisfaction pharmacy services in the Baptist Hospital. It is related to the users'perception on the quality dimension of pharmaceutical ministry. Moreover, to determine whether the level of users' satisfaction inÂ installation services Outpatient Pharmacy (IFRJ) RSBB is influenced by insurance membership status. This study uses cross-sectional study approach. The instrument uses a questionnaire with Likert scale. Validity and reliability testing uses Cronbach Alpha and non additivity Tuckey testing. Normality testing uses One-sample chi-square. The correlation analysis uses Spearman rho, while the differences between the two groups use Two Way ANOVA analysis. There is no significant difference in gender, marital status, educational background,and employment status unless the age characteristics in which BPJS-K respondents'age were older than un-insured patients. The results show the seven dimensions of pharmaceutical care outpatient quality can be used to measure patients'satisfaction un-insured or BPJSK.However, if look closely at the component dimensions turned out to be no difference between the dimensions of information provision and waiting times services in which a group of un-insured higher scores than insured BPJS-K group. While the level of respondents'satisfaction on each quality dimension of outpatient pharmacy services is not the same between the two groups. It can be seen that the dimensions of satisfaction with lounge facilities and dimensions of satisfaction with the speed waiting time drug services in uninsured group, higher than the insured group BPJS-K.